Tsimshian materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986
Two items relating to the Tsimshian language have been identified in the C. F. Voegelin Papers. They are both in Subcollection II. They consist of Tsimshian material in the "Miscellaneous languages" folder in Series II. Research Notes, Subseries I. Eskimo-Aleutian; and a separate Tsimshian folder in Series II. Research Notes, Subseries VI. Penutian, including Mayan and Zoque.